THE INFLUENCE OF WORK LIFE BALANCE AND JOB STRESS ON JOB SATISFACTION IN HONORARY NURSES IN SOUTH BUTON DISTRICT HOSPITAL - Sarnia; Andry Stepahnie Titing; Hendrik (Multifinance, 2023)
This research aims to determine: 1 the influence of work-life balance on work fitness for hoe workers in South Buton Regency Hospital 2 the influence of work life on key keys for honorary nurses at the South Buton Regency hospital. This study uses a quantitative method approach. Data collection in the process uses statistical observation, literature study, and the distribution of questionnaires. The population in the study was 56 respondents using a sampling technique, namely the sens method. The research instrument study used the validity and reliability test with SPSS 22.0. The data analysis technique used in this research was measurement model testing (outer model) and structural model testing (inner model) with Smart PLS 4.0. Based on research results, it is known that there is a positive and significant influence between the work-life balance variable shown and the work stress variable (0.000). while the stress variable has no effect on job satisfaction, as shown by the P value of 0.368.